Cooperative-Based Economic Education: An Analysis of the Role of the Merah Putih Cooperative in Enhancing Community Economic Literacy - Anggi Amelia; Hendra Riofita (INCARE, International Journal of Educational Resources, 2026)
This study aims to analyze cooperatives, especially Koperasi Merah Putih, as an alternative medium for economic education, functioning as an “economic laboratory” for members. The method used is a systematic review of 10 journals through a strict selection protocol, focusing on data regarding financial literacy, human resource management, UMKM empowerment, and cooperative digitalization. The results show that high-quality services and cooperative education significantly improve financial risk literacy, reduce dependence on informal loans, enhance member participation, and strengthen household economic independence and resilience. Digitalization of cooperative management and the use of interactive platforms successfully expand the reach of education and increase trust among young members. In conclusion, cooperatives are not merely savings and credit institutions but effective media for economic education that build collective financial literacy and improve socioeconomic welfare for the community.